Thermal, structural and optical properties of new tungsten lead-pyrophosphate glasses - Manzani, Danilo [UNESP]; Fernandes, Roger Gomes; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Cassanjes, Fabia Castro [UNESP]; Poirier, Gael (Elsevier B.V., 2011)
Crystalline lead-pyrophosphate precursor was prepared in aqueous solution from lead nitrate and phosphoric acid and characterized by X-ray diffraction, thermogravimetry and Raman scattering. This crystalline lead-phosphate was then used to prepare glass samples in the binary system Pb(2)P(2)O(7)-WO(3). Dependence of WO(3) content on thermal, structural and optical properties were investigated by thermal analysis (DSC), Raman spectroscopy, UV-visible and near-infrared absorption and M-Line technique to access refractive index values. Incorporation of WO(3) in the lead-pyrophosphate matrix enhances the glass transition temperature and thermal stability against devitrification, favors formation of P-O-W bonds and WO(6) clusters. In addition, optical properties are strongly modified with a redshift of the optical bandgap with WO(3) incorporation as well as an increase of the refractive index from 1.89 to 2.05 in the visible. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Glass; Lead; Pyrophosphate; Tungsten